2022
DOI: 10.1037/pmu0000286
|View full text |Cite
|
Sign up to set email alerts
|

MoodyTunes: A mixed methods usability study of an app for adolescent mental health.

Abstract: Suicide is the leading cause of death in young people around the world, with depression as a major driver of these numbers. However, a substantial percentage of young people with depression do not seek professional help. As people in this demographic report listening should be to up to 5 hrs of music per day, music has the potential to serve as an effective method of reaching young people and increase their mental health literacy. MoodyTunes is an in-development mHealth app that aims to increasing mental healt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 62 publications
0
2
0
Order By: Relevance
“…To be eligible participants had to be between 13 and 25 years of age. Our previous research had involved young people within this age range and indicated few differences in response between younger participants and older ones (23). Potential participants were excluded if they demonstrated current suicidal ideation and had scores on the depression subscale of the Depression Anxiety Stress Scale (DASS-21 28); greater than 14, suggesting the presence of extremely severe depression.…”
Section: Participantsmentioning
confidence: 99%
See 1 more Smart Citation
“…To be eligible participants had to be between 13 and 25 years of age. Our previous research had involved young people within this age range and indicated few differences in response between younger participants and older ones (23). Potential participants were excluded if they demonstrated current suicidal ideation and had scores on the depression subscale of the Depression Anxiety Stress Scale (DASS-21 28); greater than 14, suggesting the presence of extremely severe depression.…”
Section: Participantsmentioning
confidence: 99%
“…Findings revealed that the app concept and its proposed features were enthusiastically received by users, but the need for an attractive visual design and clean user interface was identified. After the development of an initial prototype, a think-aloud study that included automated facial analysis data was conducted with 20 young people ( 23 ). Study findings revealed that the app was positively received, with a favourable rating being given to the ability to link to mental health resources, track mood over time and to share music that has helped.…”
Section: Introductionmentioning
confidence: 99%